Effects of cranial nerve blockage in patients with chronic migraine resistant to first-line treatment - Evcili, Gökhan; Yabalak, Ahmet (Journal of Surgery and Medicine, 2021)
Background/Aim: Migraine is a common, disabling neurological disorder and cranial nerve blocks (CNB) are used in the treatment of headaches. This study aimed to compare the effectiveness of a CNB with conventional medical treatment in patients with chronic migraine resistant to first-line treatment. Methods: This retrospective cohort study included 102 patients with chronic migraine resistant to first-line treatment who were treated in our outpatient clinic. The patients were divided into two groups as those who underwent CNB (n=67) and the control group, who were only treated with conventional drugs (n=35). Bilateral CNB was performed on the patients at baseline and in the second week. The patients’ Visual Analogue Scale (VAS) scores, number of days in pain, and the number of analgesics taken were recorded at baseline and the second month. Results: The second-month VAS scores and the number of days in pain were significantly lower than baseline in both the CNB and control groups (P<0.01, and P<0.05, respectively). However, while the number of analgesics taken in the 2nd month was lower in the CNB group, it was similar in the control group. (P<0.01, P=0.33). No significant difference was found between the groups in terms of the number of days in pain in the second month (P=0.09). The second month's VAS scores and the number of analgesics taken were significantly lower in the CNB group compared to the control group (P=0.01, P<0.01). Conclusion: Our findings indicated that the CNB was more effective than conventional treatment in patients with chronic migraine resistant to first-line treatment.